Perspectives of Muslim and Minority Canadian Youth on Hate Speech and Social Media - Arshad-Ayaz, Adeela; Naseem, M. Ayaz; Hizaoui, Hedia (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2022)
The extensive user interaction made possible by social media has both pros and cons. On the one hand, educators have been thrilled with social media’s potential in the possibility of engaging youth in debates on civil responsibility and citizenship. On the other hand, social media can also be used as a powerful weapon to marginalize and intimidate already vulnerable groups. Expressions of hate are not only hurtful to the targeted group but can also have a significant impact on the cohesion and harmony of an immigrant-based society like Canada. Our overarching objective in this paper is to understand the perspectives of marginalized Canadian youth, especially Muslim youth, regarding hate speech in online environments, and particularly on social media. In this article, we present the effects of online hate speech on marginalized youth—often the victims of hate speech—in Canada. In particular, we present effects on self-esteem and self-image, relationships with dominant group members, mental and physical health and well-being, and personal and group security.